The alternative penalties for the imprisonment punishment with short period (Al-Mansour Journal, 2023)
The research includes the point of view over the need to apply alternativepenalties of the short period imprison as a punishment , to decrease the negative effects which emerge as a result to the application to the short period imprison . The research will be a study between Iraqi penal code and some Arab and foreign penal codes .The research aims to study the determination of the conception of the alternative penalties and to emerge the impotence of these penalties . and then the clarification of the way in Iraq .The researcher asserts on the necessity of existence of a model of an Arab code project including the definition of these penalties and the manners which help to apply them instead of the imprison punishment .